Neighborhood Socioeconomic Status and Feeding Practices in Finnish preschools. Issue 5 (July 2019) - Lehto, Reetta; Lehto, Elviira; Konttinen, Hanna; Vepsäläinen, Henna; Nislin, Mari; Nissinen, Kaija; Vepsäläinen, Ciara; Koivusilta, Leena; Erkkola, Maijaliisa; Roos, Eva; Ray, Carola
Aims: Certain feeding practices, such as role modeling healthy eating and encouragement are recommended to be used in preschools. Little is known about whether preschool characteristics are associated with the use of these feeding practices. Our aim was to examine whether the socioeconomic status (SES) of the preschool neighborhood is associated with the feeding practices in preschools. Methods: This study was part of the cross-sectional DAGIS study. We studied 66 municipal preschools and 378 early childhood educators (ECEs). Preschool neighborhood SES was assessed with map grid data. Feeding practices were assessed by questionnaires and lunchtime observation. Associations between preschool neighborhood SES and feeding practices were tested with logistic regression analyses adjusted for ECEs' educational level and municipal policies on ECEs' lunch prices, and on birthday foods. Results: The crude model showed that in high-SES neighborhood preschools ECEs were more likely to eat the same lunch as the children (OR 2.46, 95% CI 1.42–4.24) and to reward children with other food for eating vegetables (OR 2.48, 95% CI 1.40–4.41). Furthermore, in high-SES preschools it was less likely that birthday foods outside of the normal menu were available on birthdays (OR 0.29, 95% CI 0.12–0.71). In the adjusted model, rewarding with other food remained associated with preschool neighborhood SES (OR 2.13, 95% CI 1.12–4.07). Conclusions: After adjustments, preschool neighborhood SES was mostly unassociated with the feeding practices in preschools. Municipal policies may have a significant impact on feeding practices and ultimately on young children's food intake in Finland where most children attend municipal preschools.